Growth, stomata aperture, biochemical changes and branch anatomy in mango (Mangifera indica) cv. Chokanan in response to root restriction and water stress - Sakimin, Siti Zaharah; Ismail, Mohd Razi (Elsevier, 2009)
Mango production is often subject to space and tree size management pressures among growers. This study found that root restriction contributed to reduced leaf expansion, thus inhibiting the growth of mango trees. There was even less leaf expansion under water stress conditions. Under well-watered conditions, restricted roots considerably reduced stomatal conductance and leaf water potential compared to control root growth. More rapid reductions in stomatal conductance and leaf water potential occurred under restricted root and water stress conditions compared to control trees. Leaf proline concentrations and abscisic acid (ABA) levels increased as a result of root restriction and water stress but decreased with re-watering. Re-watering also increased stomatal conductance, leaf water potential and peroxidase accumulation in plants with both restricted and non-restricted root growth. Anatomical studies of cross sections of secondary branches showed that root restriction and water stress brought about various changes: compacted cells, as estimated by epidermis thickness and area, as well as by cortex thickness, but with increases in schelerenchyma thickness, phloem and xylem thickness, schelerenchyma area, and pith area and diameter. These results suggest that reduction of soil volume and water stress could effectively control tree size through physiological and morphological changes; thereby bringing higher sustainable returns per hectare and greater effectiveness in orchard management.